Corporate governance, financial markets, and economic growth: Does corporate governance moderate the finance-growth nexus? - Kilinc, Mustafa; Ulussever, Talat (Economics and Business Review, 2025)
This paper examines whether corporate governance plays a moderating role in the impact of financial development on economic growth. It collects a dataset of 39 advanced and developing countries for the 2006-2020 period. The empirical results show that the credit-to-GDP ratio is negatively associated with economic growth, and this finding is consistent with the literature showing the relevance of "too much finance". The main findings indicate that the negative growth impact of credits is attenuated by corporate governance as measured by minority investor protection and disclosure extent. This moderating effect is economically significant and holds for different country groups and horizons. Hence, the paper argues that corporate governance measures the quality of financial markets, while credit ratio measures its quantitative dimension. Therefore, it shows that both quality and quantity dimensions need to be taken into account to understand the finance-growth nexus properly.